Analysis Of The Formulation Of Criminal Provisions In Law Number 12 Of 2012 Concerning Higher Education - Ade Adhari; Imelda Martinelli; Indah Siti Amelia; Leony Sondang (Faculty of Law, Universitas Jenderal Soedirman, 2023)
The criminal determination legislation policy in Law no. 12 of 2012 concerning Higher Education is a part of the stages of crime prevention in the field of higher education which is expected to be able to provide clear directions for law enforcement officials at the application and execution stages of a crime by providing complete sentencing rules. However, it turns out that the criminal provisions in the law are only an incomplete or partial set of tools in the context of tackling criminal acts in the field of higher education. This can be seen from the many juridical problems in the law, including the absence of juridical qualifications, corporate criminal responsibility issues and so on. For this reason, in the future it is necessary to update the existing criminal provisions formulation policy in the Higher Education Law.Keywords: Criminal Law Policy; Formulation; Juridical Issues